2016
DOI: 10.1017/s1751731116000331
|View full text |Cite
|
Sign up to set email alerts
|

Pasture intake and milk production of dairy cows rotationally grazing on multi-species swards

Abstract: Increasing plant species diversity has been proposed as a means for enhancing annual pasture productivity and decreasing seasonal variability of pasture production facing more frequent drought scenarios due to climate change. Few studies have examined how botanical complexity of sown swards affects cow performance. A 2-year experiment was conducted to determine how sward botanical complexity, from a monoculture of ryegrass to multi-species swards (MSS) (grasses-legumes-forb), affect pasture chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…Roca-Fernández, Peyraud, Delaby, and Delagarde (2016) found that cows rotationally grazing a multispecies sward (grasses, clovers and forbs) ate 14.5% more DM, 12% more digestible OM, and produced 13%-21% more milk and 12%-15% more milk solids per day than cows grazing a single species sward of perennial ryegrass. These findings show that increasing sward botanical complexity under similar grazing management can have positive effects on animal performance (Roca-Fernández et al, 2016).…”
Section: Increasing Dry Matter Intakementioning
confidence: 97%
“…Roca-Fernández, Peyraud, Delaby, and Delagarde (2016) found that cows rotationally grazing a multispecies sward (grasses, clovers and forbs) ate 14.5% more DM, 12% more digestible OM, and produced 13%-21% more milk and 12%-15% more milk solids per day than cows grazing a single species sward of perennial ryegrass. These findings show that increasing sward botanical complexity under similar grazing management can have positive effects on animal performance (Roca-Fernández et al, 2016).…”
Section: Increasing Dry Matter Intakementioning
confidence: 97%
“…However, experiments on grass-legume interactions (typically using only a single grass species and a single clover species) have been carried out for many decades, including interactions with temperature and nitrogen supply [71][72][73], grazers [15] and FACE-studies of responses of grasses and legumes to elevated CO 2 and fertilisation [74]. Also, there have been experiments examining the effect on cow milk production and ruminant meat quality of grazing the animals on grasslands of differing species composition and richness (e.g., [75][76][77] and studies mentioned in the Introduction).…”
Section: Data and Inferences From Experimental And Observational Studiesmentioning
confidence: 99%
“…Basado en estos resultados se puede inferir que el método agronómico, aparte de ser una técnica práctica y económica, permite obtener estimaciones confiables del CMS. Es así como lo reporta Roca et al (2016), quienes utilizaron el método agronómico para estimar el CMS de animales pastoreando SSP, encontrando un mayor consumo en los animales que pastoreaban potreros con una mayor complejidad botánica, de cuatro a cinco especies forrajeras.…”
Section: Técnicas Basadas En La Pastura: Método Agronómicounclassified